L312, a novel PPARγ ligand with potent anti-diabetic activity by selective regulation - Xie, Xinni; Zhou, Xinbo; Chen, Wei; Long, Long; Li, Wei; Yang, Xiuyan; Li, Song; Wang, Lili (Biochimica et biophysica acta, 2015)
Selective PPARγ modulators (sPPARγM) retains insulin sensitizing activity but with minimal side effects compared to traditional TZDs agents, is thought as a promising strategy for development of safer insulin sensitizer. We used a combination of virtual docking, SPR-based binding, luciferase reporter and adipogenesis assays to analyze the interaction mode, affinity and agonistic activity of L312 to PPARγ in vitro, respectively. And the anti-diabetic effects and underlying molecular mechanisms of L312 was studied in db/db mice. L312 interacted with PPARγ-LBD in a manner similar to known sPPARγM. L312 showed similar PPARγ binding affinity, but displayed partial PPARγ agonistic activity compared to PPARγ full agonist pioglitazone. In addition, L312 displayed partial recruitment of coactivator CBP yet equal disassociation of corepressor NCoR1 compared to pioglitazone. In db/db mice, L312 (30mg/kg·day) treatment considerably improved insulin resistance with the regard to OGTT, ITT, fasted blood glucose, HOMA-IR and serum lipids, but elicited less weight gain, adipogenesis and hemodilution compared with pioglitazone. Further studies demonstrated that L312 is a potent inhibitor of CDK5-mediated PPARγ phosphorylation and displayed a selective gene expression profile in epididymal WAT. L312 is a novel sPPARγM. L312 may represent a novel lead for designing ideal sPPARγM for T2DM treatment with advantages over current TZDs. •L312 is identified and characterized as a novel selective PPARγ modulator.•L312 displayed a selective regulation of PPARγ target genes expression pattern.•L312 potentiated potent inhibition of Ser273 phosphorylation of PPARγ.